The role of ICT in enhancing the autonomy of higher education students: Teachers’ insights - Simões, Dora; Faustino, Paula (Education Policy Analysis Archives, 2019)
This article reflects on the insights of higher education teachers about the role that information and communication technologies (ICT) can have in enhancing students' autonomy in the teaching and learning process. In order to accomplish this goal, it was necessary to build a theoretical framework that explored the context of higher education under the assumptions of the Bologna process and educative policies, exploring the encouragement to students’ autonomy and the use of ICT in the teaching and learning process. A quantitative exploratory approach was adopted with the purpose of collecting the insights of teachers involved in two courses of the Portuguese public higher education. The data collection was made through the curricular plans and though a survey to the teachers. With this research, we conclude that teachers reveal efforts to enhance students’ autonomy and feel motivated to use ICT in their educational practices. The most frequently mentioned motivations are that ICT facilitates the access to resources and information, innovates their practice, improves the regulation, tutoring and intervention, and in interaction and communication. Teachers also appear to hold positive perceptions on the potential of ICT to support their teaching and learning process, especially the perception of utility and ease of use of ICT.